2010
DOI: 10.1021/jf101268a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in γ-Aminobutyric Acid and Glutamate Decarboxylase Activity in Oats (Avena nuda L.) during Steeping and Germination

Abstract: Gamma-aminobutyric acid (GABA) is the principal inhibitory neurotransmitter in the central nervous system and provides beneficial effects for human and other animals health. To accumulate GABA, samples from two different naked oat cultivars, Baiyan II and Bayou I, were steeped and germinated in an incubator. The content of GABA and glutamic acid as well as the activity of the glutamate decarboxylase (GAD) in oats during steeping and germination were investigated with an amino acid automatic analyzer. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…GABA is primarily synthesised from glutamic acid by glutamate decarboxylase (GAD), but it can be also formed from polyamines via c-aminobutyraldehyde intermediate, being diamine oxidase (DAO) and amino aldehyde dehydrogenase (AMADH) the enzymes involved in the process. Several studies have demonstrated that the activity of GAD and DAO is significantly increased during germination in cereals and legumes (Xu et al, 2010;Yang et al, 2011;Xu & Hu, 2014;Gan et al, 2017), phenomenon that would explain the accumulation of GABA in quinoa sprouts. In fact, it has been reported that the suitable temperature for improving GAD activity and enhances GABA content is 30°C (Guo et al, 2011;Xu & Hu, 2014), findings that support the results of the present study.…”
Section: Impact Of Germination Conditions On Gaba Content Of Quinoa Smentioning
confidence: 99%
“…GABA is primarily synthesised from glutamic acid by glutamate decarboxylase (GAD), but it can be also formed from polyamines via c-aminobutyraldehyde intermediate, being diamine oxidase (DAO) and amino aldehyde dehydrogenase (AMADH) the enzymes involved in the process. Several studies have demonstrated that the activity of GAD and DAO is significantly increased during germination in cereals and legumes (Xu et al, 2010;Yang et al, 2011;Xu & Hu, 2014;Gan et al, 2017), phenomenon that would explain the accumulation of GABA in quinoa sprouts. In fact, it has been reported that the suitable temperature for improving GAD activity and enhances GABA content is 30°C (Guo et al, 2011;Xu & Hu, 2014), findings that support the results of the present study.…”
Section: Impact Of Germination Conditions On Gaba Content Of Quinoa Smentioning
confidence: 99%
“…Sample concentrations were calculated, based on peak areas compared to those of each of the external standards. The concentration of free amino acids was determined following the method described by Xu, Hu, Duan and Tian (2010) with some modifications. Briefly, the free amino acid extracts were filtered through a 0.45 µm of nylon syringe filter (Filtrex Technology, Singapore) prior to analysis and analyzed by a Biochrom 30 series Amino Acid Analyzer (Biochrom Ltd., Cambridge Science Park, England) with a Na-cation-exchange column (8 µm, 4.6mm × 200 mm).…”
Section: Hplc Analysis Of Individual Sugarsmentioning
confidence: 99%
“…32 Choline can modulate the basic singling processes within cells as a structural element in membranes, it is crucial in brain development for most living organisms. 33 GABA is a non-protein amino acid with four free carbons and it is also considered as the major inhibitory neurotransmitter in CNS, which was involved in the regulation of cardiovascular function and provided positive effects of many neurological disorders such as Huntington's disease, Parkinson's disease, senile dementia, seizures, and Alzheimer's disease [34][35][36] etc.…”
Section: Metabolites Patterns Of the Freshwater Sh Brain Extractsmentioning
confidence: 99%